2002
DOI: 10.1002/lsm.10058
|View full text |Cite
|
Sign up to set email alerts
|

Calcium solubility of dental enamel following sub‐ablative Er:YAG and Er:YSGG laser irradiation in vitro

Abstract: In summary, it can be stated that, although the erbium laser wavelengths apparently have the potential to increase acid resistance, their application solely for caries prevention would not appear to be sensible under the prevailing conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0
19

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 18 publications
3
52
0
19
Order By: Relevance
“…This is consistent with the outcomes of Rodriguez-Vilchis et al 30 who found that acid resistance of enamel did not increase as expected following subablative Er:YAG laser irradiation. Apel et al 31 indicated no significant difference in calcium solubility between the specimens irradiated with the subablative Er:YAG and Er,Cr:YSGG lasers and that of the control. Another study demonstrated the formation of cracks following subablative erbium laser irradiation, which might act as starting points for acid attack and thus attenuate any positive effect of laser irradiation on caries prevention.…”
Section: Discussionmentioning
confidence: 98%
“…This is consistent with the outcomes of Rodriguez-Vilchis et al 30 who found that acid resistance of enamel did not increase as expected following subablative Er:YAG laser irradiation. Apel et al 31 indicated no significant difference in calcium solubility between the specimens irradiated with the subablative Er:YAG and Er,Cr:YSGG lasers and that of the control. Another study demonstrated the formation of cracks following subablative erbium laser irradiation, which might act as starting points for acid attack and thus attenuate any positive effect of laser irradiation on caries prevention.…”
Section: Discussionmentioning
confidence: 98%
“…[7][8][9][10][11] The Er:YAG laser is able to handle dental hard tissue with high efficiency because of the high absorbability of the 2.94 m wavelength by water and dental enamel. [12][13][14] The absorbed laser energy is converted to heat that boils water in the tooth, forming high-pressure steam.…”
Section: Introductionmentioning
confidence: 99%
“…The temperatures (400-1000 • C) needed to achieve the intended carbonate loss (Zuerlein et al 1999a) will be more than sufficient to induce cracking through thermal expansion of pore water. Unwanted cracking has indeed been reported for enamel surface modification using the Er:YAG laser, but not for the CO 2 laser (Apel et al 2005(Apel et al , 2002b. In using CO 2 lasers to create acid resistant surfaces, researchers often use fluences high enough to induce melting in a thin surface layer, when no cracks would be detected.…”
Section: The Effect Of Different Water-pore Sizesmentioning
confidence: 99%